ASSOCIATION OF BLOOD LIPID AND GLUCOSE LEVELS WITH CAROTID INTIMA MEDIA THICKNESS - Bokhari, Syed Aown Raza; Khan, Sikandar Hayat; Hanif, Muhammad Shahzad; Hassan, Mariam; Azam, Naila (Journal of Postgraduate Medical Institute, 2013)
Objective: To measure the differences in CIMT across groups based upon normal and higher levels offasting glucose and lipids. Methodology: This cross sectional study was carried out between January to June 2011 at department ofradiology and pathology, PNS Rahat hospital Karachi. From a target population of patients presenting forfasting blood glucose measurement, a total 0f 201 subjects were shortlisted and consented after variousexclusion. These patients were sampled for glucose and lipids after brief clinical evaluation. Later subjectsunderwent CIMT measurement in radiology department. Results: Age showed moderate positive correlation with CIMT readings (r=0.493, p=0.000), while BMI(r=0.038, p=0.636), fasting blood glucose (r=0.038, p=0.646), triglyceride (r=0.179, p=0.029), and totalcholesterol (r=0.221, p=0.007) showed lesser correlations. Patients with hyperglycemia had higher CIMT[{Group-1, Normolycemia, FBG<5.5mmol/L = 0.667+0.137cm} {Group-2, Hyperglycemia, FBG>5.5mmol/L= 0.7180+0.147cm}(p=0.028)]. Mean CIMT values among subjects with hypertriglyceridemia andhypercholesterolemia were higher than patients with normal triglycerides and cholesterol [(triglyceride:p=0.040) (total cholesterol: p=0.055)]. Conclusion: The carotid intima medial layers were found to be thicker in subjects having higher bloodlevels of fasting blood glucose, triglycerides and total cholesterol.